TUMOR-INDUCED STROKE: DIAGNOSTIC INSIGHTS FROM NEUROIMAGING (Western European Journal of Medicine and Medical Science, 2026)
Despite the widespread use of advanced radiologic imaging techniques in neurosurgical practice, the diagnosis and management of various brain tumors (BT) remain significant challenges for clinicians and healthcare systems. This is largely due to the high incidence of both primary and metastatic brain tumors, the considerable rate of unfavorable outcomes, and the substantial financial burden associated with their treatment. In addition, brain tumors may lead to serious cerebrovascular complications, including ischemic and hemorrhagic stroke, resulting from vascular compression, tumor invasion, hypercoagulability, or treatment-related effects. Early and accurate radiologic assessment plays a crucial role in detecting tumor-related stroke and guiding appropriate therapeutic strategies.